Employee Management System For SMK Ilhami Aikmel with Role-Based Access Control (RBAC) - Atiqah Baharuddin; Abdullah, Zubaile (Applied Information Technology And Computer Science, 2025)
Efficient management of employees is essential for the smooth operation of organization. Employee management at SMK Ilhami Aikmel currently relies on manual processes, causing inefficiencies and security risks. This study develops a web-based Employee Management System (EMS) with Role-Based Access Control (RBAC) to streamline staff management and secure data access. By utilizing Agile methodology, the system was designed with roles and sub-roles aligned to the school’s organizational hierarchy, ensuring precise RBAC. Testing through functional testing, security testing and user acceptance methods showed improved operational efficiency and enhanced security by restricting access based on user roles. The findings demonstrated significant improvements in operational efficiency and strengthened data security by enforcing the principle of least privilege. Future work could explore integrating additional modules and expanding the system for broader institutional use.